2007
DOI: 10.1007/s12010-007-8004-3
|View full text |Cite
|
Sign up to set email alerts
|

The Flexibility of the Non-Conservative Region at the C Terminus of d-Hydantoinase from Pseudomonas putida YZ-26 is Extremely Limited

Abstract: We previously reported that a deletion mutant (P478) with a residue Arg deleted at the C terminus of D-hydantoinase (P479) from Pseudomonas putida YZ-26 was dissociated into the monomer from its dimeric state. Based on the above result, a series of mutants of the enzyme with the C-terminal residues either deleted or substituted were prepared. The size-exclusion chromatography and bioactivity assay show that a C-terminal-substituted enzyme (R479D) and several truncated mutants (P478, P477, P476, and P475) are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…1), only the hydrogen bonds of D163eN186, E206eR479, E206eV477, and Y275eR479 as well as the salt bridges of E206eR479, E219eR479, and R223eE219 are highly conserved. Previous works indicated that the C-terminal Arg479 in bacterial hydantoinase plays an important role in dimerization [22,23]. In the present study, the structure provides the evidence that the subunit association of P. aeruginosa dihydropyrimidinase is mediated by the C-terminal Arg479 through hydrogen bonds and salt bridges.…”
Section: Monomeremonomer Interface Of P Aeruginosa Dihydropyrimidinasesupporting
confidence: 55%
See 2 more Smart Citations
“…1), only the hydrogen bonds of D163eN186, E206eR479, E206eV477, and Y275eR479 as well as the salt bridges of E206eR479, E219eR479, and R223eE219 are highly conserved. Previous works indicated that the C-terminal Arg479 in bacterial hydantoinase plays an important role in dimerization [22,23]. In the present study, the structure provides the evidence that the subunit association of P. aeruginosa dihydropyrimidinase is mediated by the C-terminal Arg479 through hydrogen bonds and salt bridges.…”
Section: Monomeremonomer Interface Of P Aeruginosa Dihydropyrimidinasesupporting
confidence: 55%
“…The native molecular mass of P. aeruginosa dihydropyrimidinase is approximately two times higher than the molecular mass of a monomer (53 kDa). Thus, we conclude that P. aeruginosa dihydropyrimidinase in solution is a stable dimer, similar to bacterial hydantoinase from P. putida YZ-26 [22,23].…”
Section: P Aeruginosa Dihydropyrimidinase As a Dimer In Solutionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous reports have shown that modifications to the C termini of DHP/HYD enzymes could decrease the enzyme activity (9, 48,[53][54][55]. In the D-HYD from B. stearothermophilus and Bacillus thermocatenulatus, the truncated enzymes with a deletion of 40 amino acids on the C terminus have lost 64% of their enzymatic activities (48).…”
Section: Structural Insights Into the Stages Of Lysine Carbamylation-mentioning
confidence: 99%
“…In the D-HYD from B. stearothermophilus and Bacillus thermocatenulatus, the truncated enzymes with a deletion of 40 amino acids on the C terminus have lost 64% of their enzymatic activities (48). In Pseudomonas putida YZ-26, a series of deletions were performed in the D-HYD and all of the truncated enzymes exhibited either low or non-detectable activities (53,54). However, CD spectroscopy showed that these deletions of the C-terminal fragment did not alter the secondary structures of the overall folding (48,54).…”
Section: Structural Insights Into the Stages Of Lysine Carbamylation-mentioning
confidence: 99%